2011
DOI: 10.1021/jp2082853
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Untethered ZnTPP–Fullerene Complexes in Solution

Abstract: The spectroscopy and dynamic behavior of the self-assembled, Soret-excited zinc tetraphenylporphyrin (ZnTPP) plus fullerene (C(60)) model system in solution has been examined using steady state fluorescence quenching, nanosecond time-correlated single photon counting, picosecond fluorescence upconversion, and picosecond transient absorption methods. Evidence of ground state complexation is presented. Steady-state quenching of the S(2) and S(1) fluorescence of ZnTPP by C(60) reveals that the quenching processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 76 publications
3
31
0
1
Order By: Relevance
“…The plot of ratio of fluorescence intensities versus concentration of HAs (Stern–Volmer plot) after correction for inner filter effect produced a straight line; this result confirmed that only one type of quenching, i.e. either static or dynamic quenching, was present . Dynamic quenching occurs when there is molecular collision between quencher and fluorophore in the excited state, such that photon emission does not happen when the two reach ground state.…”
Section: Methodssupporting
confidence: 63%
“…The plot of ratio of fluorescence intensities versus concentration of HAs (Stern–Volmer plot) after correction for inner filter effect produced a straight line; this result confirmed that only one type of quenching, i.e. either static or dynamic quenching, was present . Dynamic quenching occurs when there is molecular collision between quencher and fluorophore in the excited state, such that photon emission does not happen when the two reach ground state.…”
Section: Methodssupporting
confidence: 63%
“…In addition, the LUMO levels of suitably functionalized fullerenes can be adjusted to be between the LUMO of the porphyrins/phthalocyanines and the CB of TiO 2 . Although the photophysics of porphyrin/phthalocyanine‐fullerene complexes, and their application in solar cells,, have been studied, these conjugates have not been applied in photocatalytic systems with TiO 2 . Therefore, we decided to explore this possibility using a new anchoring compound, namely bis (4‐pyridyl) pyrrolidinofullerene ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…56 Similarly, the absorption spectrum of the radical cation of those systems do not differ much, with an intense band peaking after Soret band of neutral system and a weak and broad one after Q band of neutral system. TTC being a similar kinds of tetrapyrolic system, the characteristic absorption spectra of its radical anion or radical cation should contain an intense band in between 440-470 nm.…”
Section: Femtosecond Time Resolved Absorption Spectramentioning
confidence: 95%